Variations in procedures for ureterolysis with sharp dissection in minimally invasive hysterectomy - Yasuhito Tanase; Mayumi Kobayashi Kato; Masaya Uno; Mitsuya Ishikawa; Tomoyasu Kato (Gynecology and Minimally Invasive Therapy, 2022)
To safely perform minimally invasive hysterectomy (MIH), including laparoscopic hysterectomy and robot-assisted hysterectomy, partial ureterolysis, or visualizing only the ureter without dissection is often inadequate. Moreover, careless blunt dissection could injure the blood vessels. We present our surgical method for ureterolysis using sharp dissection during MIH. First, the outer portion of the ureter is dissected. Dissecting between the pelvic sidewall and the posterior leaf of the broad ligament creates a pararectal space outside the ureter, enabling the easy identification of the ureter running on the posterior leaf. Second, the inner portion of the ureter is dissected. After determining the location of the ureter, a better partial dissection of the ureter can be performed from the posterior leaf, instead of dissecting along the entire circumference. If fine surgery has to be performed, the ureter can be dissected by enclosing it within its sheath. We primarily perform dissections using a monopolar device, which allows a sharp dissection. Furthermore, in our method, we often include the dissection of the ureteral tunnel. It is important to understand the anatomy and membrane structure of the ureter in each patient and adjust the extent of ureterolysis based on individual differences.